Cerebellar degeneration following neuroleptic malignant syndrome. Issue 865 (November 1997) - Lal, V.; Sardana, V.; Thussu, A.; Sawhney, I. M.; Prabhakar, S.
Abstract : A 55-year-old woman with a history of bipolar affective disorder developed hyperpyrexia, rigidity and depressed consciousness (neuroleptic malignant syndrome) after commencing neuroleptic therapy. On regaining consciousness, she was mute and had signs suggesting pancerebellar involvement. Hyperpyrexia, which is a cardinal feature of neuroleptic malignant syndrome, may have caused cerebellar damage. Neuroleptic malignant syndrome needs both early recognition and prompt treatment to obviate devastating complications.